Modeling the Dynamics of Supraglacial Rivers and Distributed Meltwater Flow With the Subaerial Drainage System (SaDS) Model. Issue 12 (30th November 2021) - Hill, Tim; Dow, Christine F.
Abstract: Meltwater produced at the surface of glaciers and ice sheets has important implications for basal sliding rates and therefore ice flow velocities. In order to determine the role of supraglacial water in ice dynamics and predict future changes, we first need to understand and be able to accurately predict moulin input rates. To this end, we present the Subaerial Drainage System (SaDS) model. SaDS is a dynamic model that couples supraglacial runoff in the bare‐ice ablation zone in a distributed sheet with flow in discrete channels. Flow in the distributed sheet drives melt through potential energy dissipation, allowing a channel network to form naturally with no prior assumptions about channel locations. We apply the model to a synthetic ice sheet margin and carry out a suite of sensitivity tests. Modeled moulin inputs show expected behaviors including large diurnal variability, multi‐hour lags following peak surface melt, and demonstrate complex and diverse seasonal dynamics. The sensitivity tests illustrate the range of possible model behaviors and constrain the parameter values for which the model predicts physically realistic moulin inputs. We also apply the model to a ∼20 × 27 km 2 catchment on the southwestern Greenland Ice Sheet using RACMO melt forcing and previously mapped moulin locations. Modeled supraglacial lake and stream locations match those mapped from Landsat 8 images, and moulin inputs show varied daily and seasonal dynamics. These results demonstrate that the model is a promising tool to provide moulin inputs for subglacial and ice dynamic studies. Plain Language Summary: Throughout the summer, the surface of glaciers is covered by a network of rivers and lakes. These rivers often drain through moulins (vertical shafts from the surface to the base of the ice that let water drain through the glacier). The rate of water flow through these moulins can change the speed at which glaciers flow since water can pool underneath the glacier, allowing the glacier to slide against the bedrock. This is important because changes to glacier flow speeds can impact the rate of sea level rise. In this study we introduce a new tool, called the Subaerial Drainage System (SaDS) model, that simulates flow through glacial surface rivers and lakes in order to calculate water input into moulins. We show that SaDS more accurately represents changes in flow into moulins caused by rivers drying up or expanding than previous simulations. SaDS is a significant step forward for making realistic predictions of moulin inputs, which will be key for determining how the world's ice sheets and glaciers change as the climate continues to warm. Key Points: SaDS dynamically models supraglacial water flow in a distributed sheet and in supraglacial channels Modeled moulin inputs show complex and heterogeneous seasonal dynamics Predicted supraglacial lake and river locations agree with mapping on the Greenland Ice Sheet